Biomarkers for alcohol abuse/withdrawal and their association with clinical scales and temptation to drink. A prospective pilot study during 4-week residential rehabilitation - Coccini, Teresa; Ottonello, Marcella; Spigno, Paola; Malovini, Alberto; Fiabane, Elena; Roda, Elisa; Signorini, Cinzia; Pistarini, Caterina (Alcohol (Fayetteville, N.Y.), 2021)
A bulk of evidence in the field of translational medicine applied to clinical toxicology and rehabilitation has highlighted the possibility of using biomarkers as a support in the diagnosis of alcohol-related diseases and in monitoring of alcohol withdrawal. In a cohort of 55 subjects admitted to a 4-week residential rehabilitation period for alcohol detoxification, we applied a complementary approach correlating novel and conventional peripheral blood and urine parameters in combination with clinical and functional evaluation, contextually considered with the patient's history. Biomarkers of oxidative, inflammatory, hepatic, and neurochemical effects paralleled by alcohol craving and clinical scale measurements were determined at two specific time points, i.e., admission and discharge. Concerning the post-discharge assessment (i.e., relapse evaluation one month after discharge), a follow-up oral interview during a clinical examination was applied to evaluate alcohol abstinence.Selected biomarkers, i.e., MCP1, F2-IsoPs, and SOD1, were altered in chronic alcoholics at admission, and then showed a clearly changing trend during hospitalization. Our findings demonstrated that these specific non-traditional biomarkers, measured together with more conventional ones (e.g., CDT, EtG, IL8, ALT, AST, GGT), could represent novel key parameters for monitoring alcohol use disorders and withdrawal, being also suggestive of the complexity of the psychoneuroimmune response to alcohol. A general improvement in psychological functioning (i.e., decreases in anxiety, depression, and psychological distress) was also revealed during the 4-week rehabilitation treatment, paralleled by an increase of well-being and positive changes in terms of scores. Moreover, a positive association between SOD1 and drink craving at admission was evidenced. Notably, both SOD1 and well-being displayed a significant relation with lower risk of alcohol relapse one month after discharge, indicating that SOD1 is a good predictor of reduced relapse probability. This 4-week residential rehabilitation protocol represents a sound strategy enabling identification of alcohol use disorders and monitoring of alcohol addiction state and withdrawal. However, it has to be emphasized that results derived from this pilot study need to be extensively validated in large and independent cohorts of subjects. •Alcohol use disorders/withdrawal were monitored during 4-week residential rehabilitation.•Complementary approach was applied by using biomarkers, clinical and functional evaluation repeatedly assessed.•MCP1, F2-IsoPs, and SOD1 were valuable biomarkers for AUD, withdrawal, and relapse.•SOD1 and well-being correlated with lower risk of alcohol relapse one month after discharge.